Processing of low level signals in mixed signal environment - a hardware design for better performance - Sharif, Atif; Potdar, Vidyasagar; Singh, Jaipal; Ahmad, R.; Nath, M.; Yang, Y. (IEEE Computer Society, 2009)
The low level signals faces many problems during their processing and digitization. The main affecting factor is the added noise during its propagation in mixed signal environment which makes very difficult to extract exact information from the signal. Additionally hardware requirement increases when we want to process these kinds of signals. In this paper, we proposed a customized hardware for this purpose. This hardware caters the problems of noise, signal integrity issues and crosstalk which directly effectsembedded circuit efficiency. The board has all the options to cater the situation where the requiredsignal is buried in the noise or having very low level amplitude. Noise elimination and crosstalk isavoided in this hardware which include high speed Field Programmable gate Array (FPGA).